Pattern Recognition Receptors in Periodontal Disease: Molecular Mechanisms, Signaling Pathways, and Therapeutic Implications - Elisabetta Ferrara; Francesco Mastrocola (Journal of Molecular Pathology)
Periodontal disease remains a significant global health concern, characterized by complex host–pathogen interactions leading to tissue destruction. This review explored the role of pattern recognition receptors (PRRs) in the pathogenesis of periodontal disease, synthesizing current knowledge on their molecular mechanisms and potential as therapeutic targets. We examined the diverse family of PRRs, focusing on toll-like receptors (TLRs) and NOD-like receptors (NLRs), elucidating their activation by periodontal pathogens and subsequent downstream signaling cascades. This review highlights the intricate interplay between PRR-mediated pathways, including NF-κB and MAPK signaling, and their impact on inflammatory responses and bone metabolism in periodontal tissues. We discussed the emerging concept of PRR crosstalk and its implications for periodontal homeostasis and disease progression. Furthermore, this review addressed the potential of PRR-targeted therapies, exploring both challenges and opportunities in translating molecular insights into clinical applications. By providing an overview of PRRs in periodontal health and disease, this review aims to stimulate future research directions and inform the development of novel diagnostic and therapeutic strategies in periodontology.